2015
DOI: 10.1159/000438741
|View full text |Cite
|
Sign up to set email alerts
|

Association between Macrophage Migration Inhibitory Factor Gene Variation and Response to Glucocorticoid Treatment in Sudden Sensorineural Hearing Loss

Abstract: Several lines of evidence suggest the role of the immune system in the pathogenesis of sudden sensorineural hearing loss (SSNHL). Macrophage migration inhibitory factor (MIF) mediates its role in various immune and inflammatory conditions by the regulation of immune reactions. Several studies have confirmed an association between MIF gene polymorphisms and susceptibility to various inflammatory and autoimmune disorders. The aim of this study was to explore the association between the MIF (-173 G/C) polymorphis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
1
5
2
Order By: Relevance
“…Our results are in accordance with another report, in which the frequency of MIF À173C allele carriers was significantly elevated in SSNHL patients who responded to glucocorticoid treatment compared with those who did not respond. 20 Our results are in contrast to other reports that the À173C allele and MIF promote glucocorticoid resistance in various inflammatory diseases. 13 MIF itself is an inflammatory cytokine that has the potential to aggravate hearing loss, as shown by higher serum TNFa in SSNHL patients with the À173C allele.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results are in accordance with another report, in which the frequency of MIF À173C allele carriers was significantly elevated in SSNHL patients who responded to glucocorticoid treatment compared with those who did not respond. 20 Our results are in contrast to other reports that the À173C allele and MIF promote glucocorticoid resistance in various inflammatory diseases. 13 MIF itself is an inflammatory cytokine that has the potential to aggravate hearing loss, as shown by higher serum TNFa in SSNHL patients with the À173C allele.…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, in our results, only this group of patients showed significantly higher improvement in low‐frequency hearing than in high‐frequency hearing threshold. This is not consistent with the previous view that immune‐related hearing loss is more effective 8,30,31 …”
Section: Discussioncontrasting
confidence: 92%
“…The reason for the tendency toward a better recovery in diabetic patients in our study is speculated to be due to differences in pathophysiology between diabetic patients and non-diabetic patients, although the cause remains unclear. For example, Yandani et al reported that the genotype of macrophage migration inhibitory factor (MIF) was associated with the response to glucocorticoid treatment in patients with idiopathic SSNHL [16], and that gene polymorphism of c.À173G>C was also related to the risk of diabetes [17]. Further study is needed to clarify the association between diabetes mellitus and sudden hearing loss.…”
Section: Analysis Of Factors Associated With the Prognosis Of Idiopatmentioning
confidence: 99%